Blooming history of the Costa Rican bamboos - Pohl, Richard W (Universidad de Costa Rica, 1991)
This paper lists the eight genera and 37 species of known wild ligneous bamboos of Costa Rica and six genera of cultivated foreign bamboos. The account is based upon herbarium specimens and the author's field experiences over 24 years. Localities and dates of herbarium collections are indicated, along with the dates of vegetative and blooming collections. Successive blooming dates are known for colonies of Rhipidocladum pittieri along the Río Virilla are 1891, 1973, and 1989. Successive dates of bloom for an individual colony of R. racemiflorum at Río Chiquito are 1973 and 1989.